La Ode Muhammad Idrus Qaimuddin Sastrawan Sufi Ternama di Buton Abad XIX - La Niampe (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This article talk about the characterization of La Ode Muhammad Idrus Qaimuddin as a popular mystical in Buton in XIX century. Among the mystical characters at his period, he known as a productive writer. His works in mysticism side was written in some languages (Wolio language, Malay, and Arabic). On of his popular poem entitled